Endovascular treatment of pseudoaneurysm of the thoracic aorta from a firearm injury - Petrucci, Orlando; De Oliveira, Pedro Paulo Martins; Martins, Antonio Sérgio [UNESP]; Vieira, Reinaldo Wilson (Oxford University Press (OUP), 2008)
A 24-year-old male patient was the victim of a firearm wound that penetrated the thorax. He arrived at another hospital hemodynamically unstable and was submitted to exploratory surgery by means of bithoracotomy. A lesion of the left branch of the pulmonary artery was detected and successfully repaired. He was submitted for computer-aided tomography on the fifth postoperative day, and a lesion of the mid-thoracic aorta was detected, which formed a saccular image. Considering that the patient had already been submitted to a bithoracotomy and that a direct approach to repair would involve another thoracotomy within a short period of time, endovascular treatment was chosen in our hospital. The procedure was performed under fluoroscopy. A second computer-aided tomography indicated adequate treatment of the lesion, with no indication of an endoleak. He has undergone ambulatory follow-up for 36 months without any problem related to the procedure. While endovascular treatment of the aorta has developed enormously, multicenter studies are needed to better define the long-term results of this approach. © 2008 Published by European Association for Cardio-Thoracic Surgery. All rights reserved.
Keywords: Aorta; Gunshot wounds; Penetrating wounds; Pseudoaneurysm; adult; aorta disease; artery disease; case report; computer assisted surgery; endoleak; endovascular surgery; false aneurysm; fluoroscopy; follow up; gunshot injury; hemodynamics; hospital discharge; human; lung artery; male; penetrating trauma; postoperative complication; postoperative period; priority journal; surgical technique; thoracic aorta; thoracotomy; Adult; Aneurysm, False; Aortic Aneurysm, Thoracic; Blood Vessel Prosthesis Implantation; Humans; Male; Stents; Surgical Procedures, Minimally Invasive; Tomography, X-Ray Computed; Treatment Outcome; Wounds, Gunshot